Mettā ṭīkā : ṅāʺ rā nhacʻ chayʻ rhacʻ svayʻ mettā nhaṅʻʹ tacʻ thoṅʻʹ ṅāʺ rā kilesā kui pra chui pā saññʻ - ʼOṅʻ Kyoʻ Hinʻʺ (Thvanʻʺ Lha Kyoʻ Cā pe, 1994)
On universal love and love for the opposite sex as viewed in Buddhism.